Studies on Complex Arylhydrazones, Part v - Prasad, N.; Srivastava, A.K.; Sahay, A. (Asian Journal of Chemistry, 2010)
Complexes of the type [CuL(OH)(H2O)], [NiL(NH3)(OH)] and [HgLCl (H2O)2] where HL = pentane-2,3,4-trioxo-3-phenylhydrazone and six related phenylhydrazones containing electron releasing as well as electron withdrawing substituents in phenyl nucleus were synthesised. Their structures were assigned on the basis of elemental analysis, thermal analysis, magnetic moment, IR, UV -VIS, PMR and ESR spectral data.